ثورة بني مناصر 1871 من خلال الكتابات الفرنسية - بودن غانم (University Of Eloued جامعة الوادي, 2023)
تعالج هذه الورقة ثورة بني مناصر سنة 1871 من خلال الكتابات الفرنسية وتهدف إلى إبراز طريقة تناول الفرنسيين لحركات المقاومة الوطنية وأسبابها، حيث حاولوا إفراغها من بعدها الوطني التحرري وربطوها بالخلافات بين القيادات الجزائرية والمصالح الشخصية. والمتتبع لثورات القرن التاسع عشر في الجزائر يلمس البعد الوطني فيها والرغبة التحررية لدى قادتها، كما يلمس وعيهم الكبير باستغلال الظروف الداخلية والخارجية بما يخدم القضية الوطنية والقيام بتعبئة الجماهير للتعبير عن حالة الرفض الدائم للمستعمر والتطلّع المستمر للاستقلال. This paper deals with the revolution of Beni Menacer in 1871 through French writings and aims to highlight the way the French dealt with the national resistance movements, as they tried to empty it of its national liberation dimension and linked it to the differences between the Algerian leaders. Those who follow the revolutions of the nineteenth century in Algeria feel the national dimension and the liberation desire of its leaders, as well as their great awareness of exploiting internal and external conditions to serve the national cause and expressing the state of permanent rejection of the colonizer and the continuous aspiration for independence.
Keywords: بني مناصر; المقاومة; البركاني; ثورة 1871; Beni Menacer; resistance; El Berkani; Revolution of 1871